Growth and Content of Flavonoids of Mustard Greens (Brassica juncea L.) with Different Humic Acid and Water Content - Tia Setiawati; Nurul Khofifah; Mohamad Nurzaman; Rusdi Rusdi (Pro-Life, 2025)
Water deficiency disrupts metabolic pathways and reduces plant growth. The high demand for Brassica juncea (L.) due to its nutritional value necessitates improved cultivation practices to ensure high-quality yields. Although humic acid is known to support plant productivity, studies examining its interaction with soil moisture levels in B. juncea remain limited. This study aimed to determine the optimal soil moisture level and humic acid dosage for enhancing the growth and flavonoid content of B. juncea (L.). The experiment was conducted using a Randomized Block Design (RBD) with two factors: four levels of humic acid dosage (0 g/kg, 4 g/kg, 8 g/kg, and 12 g/kg) and four watering treatments based on field capacity (FC), namely 20%, 40%, 60%, and 80%, each with four replications. Observations were made 42 days after planting, covering plant height, number of leaves, leaf area, dry weight, and total flavonoid content. Data were analyzed using ANOVA at a 95% confidence level, and significant differences among treatments were further tested using Duncan’s Multiple Range Test (DMRT). The results showed that the treatment combination of 20% FC and 12 g/kg humic acid produced the highest values for growth and flavonoid content of B. juncea L. under drought stress conditions, with plant height (23.67 cm), number of leaves (8 leaves), leaf area (1,022 cm²), dry weight (0.55 g), and total flavonoid content (0.108 mg QE/g sample).